2017
DOI: 10.1007/s00436-017-5632-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of free-living amoebae in soils and their associated human opportunistic bacteria

Abstract: Free-living amoebae (FLA) are ubiquitous protozoa found worldwide in the environment. They feed by phagocytosis on various microorganisms. However, some bacteria, i.e., amoebae-resistant bacteria (ARB) or bacterial endocytobionts, can resist phagocytosis and even multiply inside FLA. This study investigated the diversity of culturable FLA in various soils from agricultural and mining sites and their bacterial endocytobionts. FLA were cultured on non-nutrient agar with alive Escherichia coli and identified by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 64 publications
0
32
0
1
Order By: Relevance
“…In general, Proteobacteria were within the most common bacteria in soils and aquatic environments in different countries (Denet et al . 2017 ; Hosen et al . 2017 ; Naghoni et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, Proteobacteria were within the most common bacteria in soils and aquatic environments in different countries (Denet et al . 2017 ; Hosen et al . 2017 ; Naghoni et al .…”
Section: Introductionmentioning
confidence: 99%
“…Many of the predominant amoebae in those soils are Tetramitus , Acanthamoeba and Naegleria (Denet et al . 2017 ; Peabody et al . 2017 ) known to be hosts for Legionellales .…”
Section: Introductionmentioning
confidence: 99%
“…Two strains (MEEB-Am6.1 and MEEB-Am6.2) were isolated by a culturable method from two different amoebal genera i.e. Micriamoeba and Tetramitus and two different soils, Vietnam and Burkina Faso, respectively [ 17 ]. Two reference strains of S .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we showed that S . maltophilia is also part of the microbiome of several free-living amoebal genera from soils collected in Burkina Faso and Vietnam [ 17 ]. However, its role in the context of amoebal interactions is poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Las FLA son organismos ubicuos que se han aislado en el medio ambiente del suelo (Reyes-Batlle et al, 2014, Denet et al, 2017, del agua (García et al, 2013;Montalbano Di Filippo et al, 2015) y del aire (Rivera et al, 1994). Además se han aislado de otros ambientes, como lentillas y estuches para guardarlas (Martín-Navarro et al, 2008;Gomes et al, 2016), aires acondicionados (Astorga et al, 2011) e incluso vegetales (Chavatte et al, 2016).…”
Section: Distribuciónunclassified